1998
DOI: 10.1097/00000658-199808000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Complications in 100 Living-Liver Donors

Abstract: ObjectiveA review of 100 living-liver donors was performed to evaluate the perisurgical complications of the procedure and thus to help quantify the risks to the donor. Summary Background DataDespite the advantages of living-donor liver transplantation (LDLT), the procedure has received criticism for the risk it imposes on healthy persons. A paucity of data exists regarding the complications and relative safety of the procedure. MethodsOne hundred LDLTs performed between November 1989 and November 1996 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
104
0
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 20 publications
2
104
0
9
Order By: Relevance
“…[18][19][20][21] Donor hospital stays routinely were less than 10 days, average donor blood losses were approximately 400 to 800 mL, and the need for heterologous blood transfusion of the donor was uncommon. Grewal et al 20 (University of Chicago, Chicago, IL) and Yamaoka et al 18 (Kyoto University, Kyoto, Japan) each reported outcomes of 100 living liver transplant donors with very similar findings. Interestingly, their data have been mirrored by smaller studies in North America 22 and Europe.…”
Section: Pediatric Living Liver Transplant Donor Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] Donor hospital stays routinely were less than 10 days, average donor blood losses were approximately 400 to 800 mL, and the need for heterologous blood transfusion of the donor was uncommon. Grewal et al 20 (University of Chicago, Chicago, IL) and Yamaoka et al 18 (Kyoto University, Kyoto, Japan) each reported outcomes of 100 living liver transplant donors with very similar findings. Interestingly, their data have been mirrored by smaller studies in North America 22 and Europe.…”
Section: Pediatric Living Liver Transplant Donor Outcomesmentioning
confidence: 99%
“…Biliary complications were the most commonly reported source of donor morbidity, with an overall incidence of 5% to 10%. 18,20,21,23 Leakage of bile prolonged donor hospitalization and was most commonly treated by percutaneous drainage; however, reoperation for the repair of biliary leaks has been reported. There are no data in the literature of long-term sequelae from biliary complications.…”
Section: Pediatric Living Liver Transplant Donor Outcomesmentioning
confidence: 99%
“…The number of psychosocial problems experienced by families 16 and the general reports of fatigue, wound pain, and so on 17 add credence to the notion that there are significant concerns for the welfare of the donor and family. These should not be undervalued.…”
mentioning
confidence: 95%
“…6 First, it increases the number of organs that are directly available. Second, most recipients receive their transplant on an elective basis and thus should experience lower morbidity and mortality rates.…”
mentioning
confidence: 99%